Otomasi proses penilaian tanah - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Pertanian UGM, 1998)
ABSTRACT Land is a basic necessity for human life to do their activities. Legally, land is the right to enjoy, use, and dispose of the physical space, subject to limitations imposed by government. Land is one of the factor of production and has value because of its production of goods and services. The valuer estimates the value of land to support information of land value. This information can be used for many purposes including the sale price in case of transfer of property, the compensation case, the mortgage credit, the rent of land or building, the insurance premium, and the tax base in property taxation (Henssen, 1988). As a consequent, there are several methods of valuation in which each method will be appropriate for one or more purposes. Computerization of land valuation assists the valuer to achieve an efficiency of processes, accurate land value result and reduce the cost compared to the manual procedures. It requires a valuation model in which shows the relationship of factors or characteristics of land that determine the value of land. This paper deals with discussion of land valuation and its aspect. It will cover the principle of supply and demand in determination of land value, land value factors, mass appraisal, and in the end of this paper will be presented the principle of computer assisted valuation (CAV), especially for property taxation applications by taking an example of the Indonesian case.